(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
This work discusses the dissemination and popularization of science in the Science Parks of Diamantina, Teófilo Otoni and the Science Center of Juiz de Fora. In this work, it is initially presented the panorama of the listed parks, their social function in educational processes, still observing their specificities. Through field research, the main characteristics and activities developed by teachers and the experiences of students participating in the projects are presented. The research results reveal that the three study sites have the objective of propagating science in an extensionist way to the internal community of the institutions that are inserted and to the general public, including children, youth and adults. Through scientific experiments carried out in a dynamic and easy-to-understand manner, the spaces are characterized as easily accessible environments and allow contact with science for an audience that would often not have this option. Therefore, it is concluded that these spaces are important for the exchange of knowledge, especially with regard to the contribution of activities developed for education and the popularization of science and technology.